2015
DOI: 10.1007/s40593-015-0067-7
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on Andes’ Goal-free User Interface

Abstract: Although the Andes project produced many results over its 18 years of activity, this commentary focuses on its contributions to understanding how a goalfree user interface impacts the overall design and performance of a step-based tutoring system. Whereas a goal-aligned user interface displays relevant goals as blank boxes or empty locations that the student needs to fill with specific content, a goal-free user interface is essentially a blank canvas, with no visual indications of the goals that should be atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…According to him most intelligent tutoring systems have no built-in mechanisms to reason interactive narrative plotts; learning scenarios in the guidance system intelligent usually abstracts narrative context to focus on educational subject matter. Embed intelligent tutoring systems in a learningcentered environment narrative requires integration with capable intelligent narrative technologies and managing interactive stories [7].…”
Section: Introductionmentioning
confidence: 99%
“…According to him most intelligent tutoring systems have no built-in mechanisms to reason interactive narrative plotts; learning scenarios in the guidance system intelligent usually abstracts narrative context to focus on educational subject matter. Embed intelligent tutoring systems in a learningcentered environment narrative requires integration with capable intelligent narrative technologies and managing interactive stories [7].…”
Section: Introductionmentioning
confidence: 99%
“…Physics education research teams have identified different problem types, frameworks for instruction, and have designed, implemented, and verified multiple pedagogical components specifically designed to improve problem-solving ability [1][2][3][4]. In particular, the cooperative group problem solving (CGPS) pedagogy developed by the Physics Education Research Group at the University of Minnesota contextualizes an explicit, five-step problem-solving strategy [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Problem-solving is recognized as an important component of the introductory physics course and science courses in general [1]. In particular, physics education research teams have identified different problem types, frameworks for instruction, and have designed, implemented, and tested multiple curricular components specifically designed to improve problem-solving ability [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%